Frankenstein - Wilberger, James; Connor, Kevin; Shelly, Mary; Hallmark Entertainment ([S.l] : Hallmark Entertainment, 2003)
In this remake of Mary Shelley's classic novel, a scientist gets in over his head, creating a monster with a mind of his own. Directed by Kevin Connor, this remake features exquisite cinematography
Title from title screen
Based on the novel'Frankenstein' by Mary Shelly
Cast: Luke Goss, Alec Newman, Julie Delpy, William Hurt, Donald Sutherland
DVD Format
With English and Chinese subtitles
Keywords: Monsters -- Drama; Frankenstein (Fictitious character) -- Drama; Horror films